Insight Into The Methodological Preparation Of A Future Foreign Language Teacher - Akramiov Shukhrat Rakhmatovich (European International Journal of Pedagogics, 2025)
The author analyzed the theoretical and practical implications and problems of preparation of a future foreign teacher. bachelor should be aimed at mastering constructive, project and heuristic competencies that allow students to organize and manage their activities in the classroom. During the preparation process, the bachelor should master the competence of teaching a foreign language, the competence of developing speech and the competence of developing speech activity in a foreign language. Methodological preparation is studied as a separate type of professional pedagogical competence in the field of methodology, defined as an integral multi-level professionally significant characteristic of a person, communication and professional activity equated with other types of psychological and pedagogical competence, pedagogical culture and serves as a means of positive pedagogical experience.